Validity and Classroom Language Testing: A Practical Approach - Giraldo, Frank D. (Colombian Applied Linguistics Journal, 2020)
Validity and validation are common in large-scale language testing. These topics are fundamental because they help stakeholders in testing systems make accurate interpretations of individuals’ language ability and related ensuing decisions. However, there is limited information on validity and validation for classroom language testing, for which interpretations and decisions based on curriculum objectives are paramount, too. In this reflection article, I provide a critical account of these two issues as they are applied in large-scale testing. Next, I use this background to discuss and provide possible applications for classroom language education through a proposed approach for validating classroom language tests. The approach comprises the analyses of curriculum objectives, design of test specifications, analysis of test items, professional design of instruments, statistical calculations, cognitive validation and consequential analyses. I close the article with implications and recommendations for such endeavours and highlight why they are fundamental for high-quality language testing systems in classroom contexts.